Stepped annular member

JP2026166180APending Publication Date: 2026-10-14NIPPON STEEL CORPORATION
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025058970
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0011】 本開示の段付き環状部材では、熱処理ひずみによる内径の変形量の軸方向におけるばらつきが小さい。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166180000001_ABST
    Figure 2026166180000001_ABST
Patent Text Reader

Abstract

To provide a stepped annular member with small variation in the amount of internal diameter deformation due to heat treatment strain. [Solution] The stepped annular member (100) is made of steel and comprises a member body (30) having a carburized layer (40) formed on its surface and a total area ratio of martensite and bainite in the core (50) of 95% or more. The member body (30) is an annular shape having a constant inner diameter and axial length h (mm) in the axial direction. The member body (30) includes a thin-walled portion (10) having a wall thickness t1 and a thick-walled portion (20) having a wall thickness t2 that is more than 1 to 3 times the wall thickness t1. In the longitudinal cross-section of the member body (30), when a band-shaped region with a width h / 25 (mm) and length h (mm) centered at a position t1 / 2 (mm) radially from the inner circumferential surface is divided into 25 rectangular regions arranged in the axial direction, the maximum value of the bainite fraction in each rectangular region is 50% or more, and the maximum difference in the bainite fraction between two adjacent rectangular regions is 5 to 15%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to a stepped annular member. [Background technology]

[0002] Annular components such as gears used in automobiles and industrial machinery are subjected to repeated high stresses. Therefore, these annular components require high wear resistance and fatigue resistance. These annular components are usually manufactured by performing a predetermined heat treatment on intermediate products made from steel. One example of a heat treatment performed in the manufacturing process of annular components is carburizing and quenching. In carburizing and quenching, the annular component is heated to a temperature above the austenite transformation temperature, and then carbon is permeated and diffused from the surface of the annular component to increase the carbon concentration of the surface layer. After that, the annular component is rapidly cooled. This causes a carburized layer to form on the surface of the annular component, which has a high solid solution carbon concentration and consists mainly of a martensitic structure. The carburized layer is harder than the structure before carburizing and quenching. Therefore, annular components with a carburized layer on the surface have increased wear resistance and fatigue resistance.

[0003] On the other hand, during carburizing and quenching, thermal stress due to temperature changes and stress due to volume changes caused by phase transformation are generated in the annular member. As a result, strain occurs in the annular member, causing it to deform. In this specification, the deformation of the annular member caused by carburizing and quenching is referred to as heat treatment strain.

[0004] Annular components, such as gears used in automobiles, are typically fitted with shafts or other components that contact the inner circumferential surface of the annular component and are then fixed in place. Therefore, if the inner diameter deforms due to heat treatment strain, the inner circumferential surface must be ground down to a predetermined size. This increases the manufacturing cost and lead time of the annular component. Furthermore, if there is significant variation in the amount of deformation of the inner diameter in the axial direction of the annular component, variations will also occur in the amount of carburized layer removed by grinding the inner circumferential surface. As a result, variations in hardness occur on the inner circumferential surface of the annular component, significantly reducing its wear resistance and fatigue resistance. Therefore, technologies to reduce heat treatment strain in annular components are needed.

[0005] A technique for reducing heat treatment distortion of annular members is proposed, for example, in Japanese Patent Publication No. 2019-143211 (Patent Document 1). Patent Document 1 discloses an annular gear made of steel with a through hole formed therein for fixing a shaft. This annular gear comprises a cylindrical portion having a pair of annular end faces provided at both ends in the axial direction of the through hole, an inner circumferential surface connecting the inner edges of the pair of end faces, and an outer circumferential surface connecting the outer edges of the pair of end faces, and a plurality of teeth provided on the outer circumferential surface of the cylindrical portion, and the hardness of each pair of end faces is 300 HV or more lower than the hardness of the inner circumferential surface and the outer circumferential surface. Patent Document 1 states that this makes it possible to suppress large differences in the inner diameter depending on the position in the axial direction. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Japanese Patent Publication No. 2019-143211 [Non-patent literature]

[0007] [Non-Patent Document 1] The Japan Institute of Metals (ed.), "Metal Data Book," 4th revised edition, Maruzen Co., Ltd., February 2004, p. 166. [Non-Patent Document 2] Hasegawa et al., "Correlation between static intensity parameters," Materials, Vol.39 (1990) No.442, pp.859-863. [Non-Patent Document 3] Takada et al., "Component Design of Bainite-Type High-Strength Forging Steel," Steel and Iron, Vol. 88 (2002) No. 9, pp. 534-538. [Overview of the project] [Problems that the invention aims to solve]

[0008] Incidentally, the annular member may have a shape in which a tubular thin-walled portion and a tubular thick-walled portion having a wall thickness greater than that of the thin-walled portion are arranged along the axial direction. In the present specification, an annular member having such a shape is referred to as a stepped annular member. Compared with an annular member having a constant wall thickness in the axial direction, the stepped annular member tends to have a larger variation in the deformation amount of the inner diameter due to heat treatment strain in the axial direction. Therefore, for the stepped annular member, it is required to further suppress the heat treatment strain. However, Patent Document 1 does not discuss at all the suppression of heat treatment strain of the stepped annular member.

[0009] An object of the present disclosure is to provide a stepped annular member in which the variation in the deformation amount of the inner diameter due to heat treatment strain in the axial direction is small. [Means for Solving the Problems]

[0010] A stepped annular member of the present disclosure includes an annular member main body. The member main body is made of steel. The member main body has a constant inner diameter in the axial direction and an axial length of h (mm). A carburized layer is formed on the surface layer of the member main body. In a region inside the carburized layer of the member main body, the total area ratio of the hard structure composed of martensite and / or bainite is 95% or more. The member main body includes a thin-walled portion and a thick-walled portion. The thin-walled portion has an annular shape with a wall thickness t1 (mm). The thick-walled portion is arranged coaxially with the thin-walled portion and in contact with the thin-walled portion. The thick-walled portion has an annular shape with a wall thickness t2 (mm) that is more than 1 time to 3 times the wall thickness t1. In the stepped annular member of the present disclosure, among the cross sections of the member main body that include the central axis of the member main body and are arranged apart from each other on both sides of the central axis, in one cross section, when a strip-shaped region having a radial width of h / 25 (mm) centered at a position t1 / 2 (mm) in the radial direction from the inner peripheral surface of the member main body and an axial length of h (mm) is divided into 25 rectangular regions arranged in the axial direction, the maximum value of the bainite fraction in each rectangular region is 50% or more, and the maximum value of the difference in the bainite fraction between two adjacent rectangular regions is 5 to 15%. [Effects of the Invention]

[0011] In the stepped annular member of this disclosure, the axial variation in the amount of deformation of the inner diameter due to heat treatment strain is small. [Brief explanation of the drawing]

[0012] [Figure 1] Figure 1 is a perspective view of the stepped annular member of this embodiment. [Figure 2] Figure 2 is a plan view of the stepped annular member of this embodiment. [Figure 3] Figure 3 is a plan view of a stepped annular member having a main body with spline processing on its inner surface. [Figure 4] Figure 4 is a longitudinal cross-sectional view of the stepped annular member of this embodiment. [Figure 5] Figure 5 is a cross-sectional view of the thin-walled portion of the stepped annular member of this embodiment. [Figure 6] Figure 6 is a cross-sectional view of a thin-walled section with multiple teeth formed on its outer circumference. [Figure 7] Figure 7 is a longitudinal cross-sectional view of the stepped annular member of this embodiment, schematically showing the band-shaped region and the rectangular region. [Figure 8] Figure 8 shows an example of the bainite fraction in each rectangular region. [Figure 9] Figure 9 shows the conditions for the carburizing and quenching treatment in the heat treatment simulation of the analysis example. [Figure 10] Figure 10 shows the heat transfer coefficient of the oil used for oil cooling in the heat treatment simulation of the analysis example. [Modes for carrying out the invention]

[0013] The inventors investigated means to reduce the axial variation in the amount of deformation of the inner diameter due to heat treatment strain in stepped annular members. Specifically, using stepped annular members with various shapes as models, they conducted heat treatment simulations in which the distribution of martensite and bainite in the stepped annular members was varied in various ways, and analyzed the amount of deformation under each condition. As a result, it was found that a stepped annular member having the following configuration can reduce the axial variation in the amount of deformation of the inner diameter due to heat treatment strain.

[0014] The stepped annular member of the first configuration comprises an annular member body. The member body is made of steel. The member body has a constant inner diameter in the axial direction and an axial length of h (mm). A carburized layer is formed on the surface of the member body. In the region of the member body inside the carburized layer, the total area ratio of the hard structure consisting of martensite and / or bainite is 95% or more. The member body includes a thin-walled portion and a thick-walled portion. The thin-walled portion is an annular shape with a wall thickness t1 (mm). The thick-walled portion is arranged coaxially with the thin-walled portion and in contact with it. The thick-walled portion is an annular shape with a wall thickness t2 (mm) which is more than 1 to 3 times the wall thickness t1. In the stepped annular member of the first configuration, the cross-section of the member body includes the central axis of the member body and is arranged in two spaced-apart sections on either side of the central axis. In one of the cross-sections, when a band-shaped region with a radial width of h / 25 (mm) and an axial length of h (mm), with the center line located at a radial distance t1 / 2 (mm) from the inner circumferential surface of the member body, is divided into 25 rectangular regions arranged in the axial direction, the maximum value of the bainite fraction in each rectangular region is 50% or more, and the maximum difference in the bainite fraction between two adjacent rectangular regions is 5 to 15%.

[0015] The stepped annular member of the second configuration is the stepped annular member of the first configuration, wherein a plurality of teeth are formed on at least one of the outer circumferential surface of the thin-walled portion and the outer circumferential surface of the thick-walled portion, along the circumferential direction of the thin-walled portion or the thick-walled portion.

[0016] The third configuration of the stepped annular member is a stepped annular member of the first or second configuration, wherein a spline groove, keyway, or screw groove is formed on the inner circumferential surface of the member body.

[0017] Embodiments of this disclosure will be described below with reference to the drawings. In each drawing, the same or equivalent components will be denoted by the same reference numerals, and redundant descriptions will not be repeated.

[0018] Figure 1 is a perspective view of the stepped annular member 100 of this embodiment. In this specification, the direction parallel to the central axis X of the stepped annular member 100 is defined as the axial direction, the direction perpendicular to the central axis X is defined as the radial direction, and the circumferential direction of a circle centered on the central axis X is defined as the circumferential direction. In this specification, the cross section obtained when cut by a plane containing the central axis X is defined as the longitudinal section, and the cross section obtained when cut by a plane perpendicular to the central axis X is defined as the transverse section.

[0019] Referring to Figure 1, the stepped annular member 100 comprises a member body 30. The member body 30 is made of steel. The chemical composition of the steel used to make the member body 30 is not particularly limited and may consist of a well-known chemical composition. For example, the chemical composition of the steel used to make the member body 30 may satisfy any one selected from the group consisting of SCM415, SCM418, SCM420, SCM421, SCM425, SCM430, SCM432, SCM435, SCM440, SCM445, and SCM822 as specified in JIS G 4053 (2018). The chemical composition of the steel may also be other than those described above.

[0020] The member body 30 is an annular shape with the central axis X as its central axis. The member body 30 includes an inner circumferential surface 31. Figure 2 is a plan view of the stepped annular member 100 of this embodiment. The inner circumferential surface 31 may be a smooth circular surface. In this case, the inner circumferential surface 31 is circular when the member body 30 is viewed from above. The diameter of the inner circumferential surface 31 when the member body 30 is viewed from above is defined as the inner diameter dI (mm) of the member body 30. The inner diameter dI of the member body 30 is constant in the axial direction. Half the value of the inner diameter dI of the member body 30 is defined as the inner radius rI (mm) of the member body 30.

[0021] Figure 3 is a plan view of the stepped annular member 100A of this embodiment, which has a different inner surface shape from the stepped annular member 100 described above. The inner surface 31 of the stepped annular member 100A is splined. In this embodiment, the inner surface 31 may be splined, keywayed, or threaded, creating irregularities. In other words, spline teeth, keyways, or threads may be formed on the inner surface 31. In these cases, the minimum diameter of the inner surface 31 when the member body 30 is viewed from above is defined as the inner diameter dI of the member body 30. For example, if the inner surface 31 is splined, the smallest diameter of the spline hole as defined in JIS B 1603:1995 is defined as the inner diameter dI of the member body 30. Specifically, as shown in Figure 3, the diameter of the virtual cylinder in contact with the portion of the inner surface 31 where no spline grooves are formed is defined as the inner diameter dI of the member body 30. Similarly, if a keyway is machined on the inner circumferential surface 31, the diameter of the virtual cylinder in contact with the portion of the inner circumferential surface 31 where the keyway is not formed is defined as the inner diameter dI of the member body 30. If threads are cut on the inner circumferential surface 31, the diameter of the virtual cylinder in contact with the threads formed on the inner circumferential surface 31 is defined as the inner diameter dI of the member body 30.

[0022] Figure 4 is a longitudinal cross-sectional view of the stepped annular member 100. The longitudinal cross-section of the stepped annular member 100 is symmetrical with respect to the central axis X, and is arranged in two spaced apart on either side of the central axis X. In Figure 4, only one of the longitudinal cross-sections of the stepped annular member 100, on either side of the central axis X, is shown. Referring to Figure 4, a carburized layer 40 is formed on the surface of the member body 30. The carburized layer 40 is a region in which carbon has penetrated from the surface due to the carburizing and quenching treatment, and the solid solution carbon concentration is higher compared to the structure before the carburizing and quenching treatment. The microstructure of the carburized layer 40 mainly consists of martensite. Here, if the carbon concentration by mass % at a depth of 100 μm from the surface of the member body 30 is 0.60% or higher, it is determined that the carburized layer 40 is formed on the surface of the member body 30.

[0023] The carbon concentration at a depth of 100 μm from the surface of the component body 30 is determined using an electron probe microanalyzer (EPMA). Specifically, a test specimen is taken from the stepped annular member 100, with the observation surface including a depth of 100 μm from the surface of the component body 30. The size of the test specimen is not particularly limited, as long as the observation surface includes a 50 μm × 50 μm measurement area with the 100 μm depth position at its center. The observation surface is parallel to the radial direction. The carbon concentration (mass%) is measured on the observation surface of the obtained test specimen using EPMA. Specifically, surface analysis is performed on the measurement area of ​​the observation surface as described above. The arithmetic mean of the carbon concentration (mass%) in the obtained measurement area is defined as the carbon concentration (mass%) at a depth of 100 μm from the surface of the component body 30. For the EPMA surface analysis, the acceleration voltage is set to 15 kV, the irradiation current to 500 nA, the electron beam diameter to 3 μm, and the measurement pitch to 3 μm.

[0024] Referring to Figure 4, the region inside the carburized layer 40 in the member body 30 is defined as the core 50. The core 50 is the region that is not affected by the intrusion and diffusion of carbon due to the carburizing and quenching process.

[0025] The core 50 has a total area ratio of 95% or more of hard tissue consisting of martensite and / or bainite. Other tissues in the microstructure of the core 50 besides martensite and bainite include, for example, ferrite, pearlite, carbides, and retained austenite.

[0026] The total area ratio of the hard tissue in the core 50 is determined by the following method. First, the total area ratio of ferrite and pearlite in the core portion 50 is determined. A test piece is taken from the main body 30 of the component, including a surface perpendicular to the axial direction as the observation surface. The observation surface includes a 1 mm × 1 mm measurement area centered on the thick-walled portion center position 23, which will be described later. The observation surface is mirror-polished. Etching is performed on the mirror-polished observation surface using 2% nitric acid alcohol (Nital etching solution). Of the etched observation surface, five arbitrary observation fields (240 μm × 180 μm) within the measurement area are observed with a 500x optical microscope. In the 500x observation field, the hard structure and ferrite and pearlite can be easily distinguished by contrast, etc. Specifically, the hard structure is observed as a phase containing substructures (lath). Ferrite does not show substructures within the grains and is observed as a region with higher brightness than the hard structure. Furthermore, because pearlite has a lamellar structure and is more strongly corroded by Nital etching solution than hard tissue, it is observed as a region with lower brightness than hard tissue. The total area of ​​ferrite and pearlite in the observation field is determined by known image processing. The total area ratio of ferrite and pearlite is determined based on the total area of ​​ferrite and pearlite identified in all observation fields and the total area of ​​all observation fields.

[0027] Next, the area ratio of carbides in the core portion 50 is determined. A test piece is taken from the member body 30, including a surface perpendicular to the axial direction as the observation surface. The observation surface includes a 1 mm × 1 mm measurement area centered on the thick-walled portion center position 23, which will be described later. The observation surface is mirror-polished. From the mirror-polished observation surface, five arbitrary observation fields (240 μm × 180 μm) within the measurement area are observed with a field emission scanning electron microscope (FE-SEM) to capture a Z-contrast image, also known as a COMPO image, from the backscattered electron detector. The observation magnification is 500x. All carbides with an equivalent circle diameter of 5 μm or more are identified from the captured photographic images. Here, the equivalent circle diameter refers to the diameter (μm) when the area of ​​the carbide is converted to a circle. Carbides with an equivalent circle diameter of less than 5 μm can be ignored as they are part of martensite and bainite. Furthermore, in contrast images, martensitic and bainite structures, which are mainly composed of iron, can be easily distinguished from carbides, which contain a large amount of carbon. The area ratio of carbides is defined as the area ratio calculated based on the total area of ​​carbides with an equivalent circle diameter of 5 μm or more identified in all observation fields and the total area of ​​all observation fields.

[0028] Furthermore, the area ratio of retained austenite in the core portion 50 is determined. A test specimen is taken from the member body 30, including a plane perpendicular to the axial direction as the measurement surface. The measurement surface includes the center position 23 of the thickened portion, which will be described later. X-ray diffraction measurement is performed on the measurement surface of the obtained test specimen. Specifically, X-rays are irradiated onto the center position 23 of the thickened portion of the measurement surface, and the X-ray diffraction intensity of each of the (110) plane of the α phase, the (200) plane of the α phase, the (211) plane of the α phase, the (220) plane of the α phase, the (200) plane of the γ phase, and the (311) plane of the γ phase is measured, and the integrated intensity of each plane is calculated. In measuring the X-ray diffraction intensity, the target of the X-ray diffractometer is set to Cu (CuKα rays), and the output is set to 40kV-400mA. After calculation, the volume fraction Vγ (%) of retained austenite is calculated for each combination (4 × 3 = 12 pairs) of each face of the α phase and each face of the γ phase using equation (I). The average value of the volume fraction Vγ of the 12 pairs of retained austenite is then defined as the area fraction (%) of retained austenite. Vγ=100 / {1+(Iα×Rγ) / (Iγ×Rα)} (I) Here, Iα is the integrated intensity of the α phase. Rα is the crystallographic theoretical calculation value of the α phase. Iγ is the integrated intensity of the γ phase. Rγ is the crystallographic theoretical calculation value of the γ phase. In this specification, Rα at the (110) plane of the α phase is set to 100, Rα at the (200) plane of the α phase is set to 14.0, Rα at the (211) plane of the α phase is set to 25.6, Rα at the (220) plane of the α phase is set to 8.4, Rγ at the (200) plane of the γ phase is set to 34.0, Rγ at the (220) plane of the γ phase is set to 17.9, and Rγ at the (311) plane of the γ phase is set to 20.5.

[0029] Finally, the total area percentage (%) of the hard tissue in the core 50 is calculated using the following formula. Total area percentage of hard tissue (%) = 100 - (Total area percentage of ferrite and pearlite (%) + Area percentage of carbides (%) + Area percentage of retained austenite (%))

[0030] Referring to Figures 1 and 4, the member body 30 includes a thin-walled portion 10 and a thick-walled portion 20. Specifically, the member body 30 is divided into a thin-walled portion 10 and a thick-walled portion 20 in cross-section.

[0031] The thin-walled portion 10 is a part of the member body 30 and is a region defined by the cross-section of the member body 30. The thin-walled portion 10 is an annular shape with the central axis X as its central axis. The thin-walled portion 10 includes an inner circumferential surface 11, which is a part of the inner circumferential surface 31 of the member body 30, and an outer circumferential surface 12. The thin-walled portion 10 further includes an end face 13 connecting the inner circumferential surface 11 and the outer circumferential surface 12. Since the inner circumferential surface 11 is a part of the inner circumferential surface 31, its inner radius is rI (mm).

[0032] Figure 5 is a cross-sectional view of the thin-walled portion 10 in the stepped annular member 100 of this embodiment. In this embodiment, the shape of the outer circumferential surface 12 in the cross-section of the thin-walled portion 10 may be circular, as shown in Figure 5. In this case, the radius of the outer circumferential surface 12 is defined as the outer radius rO1 (mm). Figure 6 is a cross-sectional view of the thin-walled portion 10 in the stepped annular member 100B of this embodiment, which has a different outer circumferential surface shape from the stepped annular member 100 and stepped annular member 100A described above. In this embodiment, as shown in Figure 6, a plurality of teeth 14 may be formed on the outer circumferential surface 12 of the thin-walled portion 10 along the circumferential direction of the thin-walled portion 10. That is, when a plurality of teeth 14 are formed on the outer circumferential surface 12 of the thin-walled portion 10, the shape of the outer circumferential surface 12 in the cross-section of the thin-walled portion 10 does not have to be circular. In this case, the radial distance from the central axis X to the tooth root 15 is defined as the outer radius rO1 (mm). In the thin-walled section 10, the difference between the outer radius rO1 (mm) and the inner radius rI (mm) is defined as the wall thickness t1 (mm) of the thin-walled section 10. Regardless of the presence or absence of multiple teeth 14, the wall thickness t1 of the thin-walled section 10 is constant in the axial direction.

[0033] Referring to Figure 4, let h1 (mm) be the axial length of the thin-walled portion 10. The axial length h1 of the thin-walled portion 10 is not particularly limited. The lower limit of the ratio of the axial length h1 to the wall thickness t1 is, for example, 0.20, 0.40, 0.60, 0.80, and 1.00. The upper limit of the ratio of the axial length h1 to the wall thickness t1 is, for example, 10.00, 8.00, 6.00, 4.00, and 3.00.

[0034] The thickened portion 20 is a part of the member body 30 and is a region demarcated by the cross-section of the member body 30. The thickened portion 20 is an annular shape with the central axis X as its central axis. In other words, the thickened portion 20 is arranged coaxially with the thinned portion 10. The thickened portion 20 is further arranged in contact with the thinned portion 10. The thickened portion 20 includes an inner circumferential surface 21, which is a part of the inner circumferential surface 31 of the member body 30, and an outer circumferential surface 22. Since the inner circumferential surface 21 is a part of the inner circumferential surface 31, its inner radius is rI (mm).

[0035] Similar to the thin-walled portion 10, the shape of the outer circumferential surface 22 in the cross-section of the thick-walled portion 20 may be circular, or multiple teeth may be formed on the outer circumferential surface 22 of the thick-walled portion 20 along the circumferential direction of the thick-walled portion 20. In other words, if multiple teeth are formed on the outer circumferential surface 22 of the thick-walled portion 20, the shape of the outer circumferential surface 22 in the cross-section of the thick-walled portion 20 does not have to be circular. If the shape of the outer circumferential surface 22 in the cross-section of the thick-walled portion 20 is circular, the radius of the outer circumferential surface 22 is defined as the outer radius rO2 (mm). If the shape of the outer circumferential surface 22 in the cross-section of the thick-walled portion 20 is not circular and multiple teeth are formed on the outer circumferential surface 22 of the thick-walled portion 20, the radial distance from the central axis X to the tooth root is defined as the outer radius rO2 (mm). In the thick-walled portion 20, the difference between the outer radius rO2 (mm) and the inner radius rI (mm) is defined as the wall thickness t2 (mm) of the thick-walled portion 20. Regardless of the presence or absence of multiple teeth, the thickness t2 of the thickened portion 20 is constant in the axial direction.

[0036] The wall thickness t2 (mm) of the thick-walled portion 20 is more than 1 to 3 times the wall thickness t1 (mm) of the thin-walled portion 10. The preferred lower limit of the ratio of wall thickness t2 (mm) to wall thickness t1 (mm) is 1.1, more preferably 1.5, and still more preferably 1.8. The preferred upper limit of the ratio of wall thickness t2 (mm) to wall thickness t1 (mm) is less than 3, more preferably 2.9, still more preferably 2.5, and still more preferably 2.2.

[0037] The axial length of the thick-walled portion 20 is denoted as h2 (mm). Here, the thin-walled portion 10 and the thick-walled portion 20 are regions that divide the member body 30 in cross-section. In other words, the axial length h of the member body 30 is expressed as the sum of the axial length h1 of the thin-walled portion 10 and the axial length h2 of the thick-walled portion 20. The axial length h2 of the thick-walled portion 20 is not particularly limited. The lower limit of the ratio of the axial length h2 to the thickness t2 is, for example, 0.10, for example, 0.20, for example, 0.30, for example, 0.33. The upper limit of the ratio of the axial length h2 to the thickness t2 is, for example, 2.00, for example, 1.50, for example, 1.30, for example, 1.10, for example, 1.00. Furthermore, the axial center position of the thick-walled portion 20, at a depth of t2 / 2 (mm) from the inner circumferential surface 21, is defined as the center position 23 of the thick-walled portion. The center position 23 of the thickened portion is included in the core portion 50.

[0038] Figure 7, similar to Figure 4, shows only one cross-section of the stepped annular member 100, straddling the central axis X. Referring to Figure 7, the thin-walled central position Y is defined as a position t1 / 2 (mm) radially from the inner circumferential surface 31 of the member body. A strip-shaped region with a radial width of h / 25 (mm) and an axial length of h (mm) centered on the thin-walled central position Y is defined as the strip-shaped region p. Furthermore, the strip-shaped region p is divided into 25 rectangular regions arranged in the axial direction. Of the 25 rectangular regions, the nth (n:1~25) rectangular region from the side closest to the end face 13 of the thin-walled portion 10 is defined as the rectangular region pn. In other words, rectangular region p1 refers to the rectangular region closest to the end face 13 out of the 25 rectangular regions, and rectangular region p25 refers to the rectangular region furthest from the end face 13 out of the 25 rectangular regions.

[0039] The stepped annular member 100 of this embodiment satisfies the following conditions. (Condition 1) The maximum value XB of the bainite fraction in rectangular region p1 to rectangular region p25. MAX The percentage is 50% or more. (Condition 2) The maximum value of the difference ΔXB in bainite fractions between adjacent rectangular regions pn and p(n+1) MAX The percentage is 5-15%. Furthermore, ΔXB can be calculated using the following formula. ΔXB = |XB n -XB n+1 | Here, XB n This is the bainite fraction (%) in the rectangular region pn, and XB n+1 This represents the bainite fraction (%) in the rectangular region p(n+1).

[0040] Figure 8 is a graph showing an example of the bainite fraction in rectangular regions p1 to p25 of the stepped annular member 100 of this embodiment. Specifically, it is a graph based on distribution D in shape number 2 in the analysis example described later. In the graph of Figure 8, the values ​​on the horizontal axis represent the value of n in rectangular region pn. Referring to the graph of Figure 8, in the band-shaped region p, the bainite fraction is maximum in the rectangular region located near the axial center of the band-shaped region p. Furthermore, from rectangular regions p1 and p25 located at the ends of the band-shaped region p, the bainite fraction gradually increases toward the rectangular region where the bainite fraction is maximum. It should be noted that in steel members having a carburized layer, where the core mainly consists of martensite and bainite, the martensite fraction tends to decrease and the bainite fraction tends to increase from the surface toward the interior of the steel member. This is well known to those skilled in the art.

[0041] In the stepped annular member 100 that satisfies condition 1, there is a region in the band-shaped region p where the bainite fraction is sufficiently high. Furthermore, in the stepped annular member 100 that satisfies condition 2, the rate of increase in the bainite fraction from the region with a low bainite fraction to the region where the bainite fraction is maximum is adjusted to an appropriate range. In other words, in the stepped annular member 100 that satisfies conditions 1 and 2, the band-shaped region p is distributed with regions where the bainite fraction is low and regions where the bainite fraction is sufficiently high, and there is no region where the bainite fraction changes abruptly. As shown in the analysis example described later, by satisfying conditions 1 and 2, the stepped annular member 100 of this embodiment reduces the axial variation in the amount of deformation of the inner diameter due to heat treatment strain.

[0042] Note that the stepped annular member 100 of the present embodiment is manufactured by subjecting an intermediate product made of steel to a well-known carburizing quenching treatment, and then subjecting it to a well-known low-temperature tempering treatment. A person skilled in the art can perform the manufacturing by appropriately changing the heating temperature, holding time and cooling rate in the carburizing quenching treatment according to the shape of the intermediate product and the hardenability of the intermediate product expected from the chemical composition of the steel, so that the manufactured stepped annular member can be adjusted to satisfy the above configuration.

[0043] The bainite fraction in each rectangular region is determined by the following method. The band-shaped region p consists of a carburized layer 40 mainly composed of martensite, and a core portion 50 in which the total area ratio of hard structures composed of martensite and / or bainite is 95% or more. Therefore, the microstructure of the band-shaped region p can be regarded as consisting of one or more selected from the group consisting of martensite and bainite. In this case, the Vickers hardness HV at any position in the band-shaped region p is the hardness HV of martensite M and the hardness HV of bainite B is expressed as a linear sum. That is, the Vickers hardness HV at any position in the band-shaped region p is expressed by the following formula (A), where XB(%) is the bainite fraction at the relevant position. HV=(1-XB / 100)×HV M +(XB / 100)×HV B (A) When formula (A) is rearranged with respect to the bainite fraction XB, the bainite fraction XB can be obtained from the following formula (B). XB=100×(HV M -HV) / (HV M -HV B ) (B)

[0044] Here, the hardness HV of martensite in the steel after low-temperature tempering MAs described in Non-Patent Literature 1, it is known to depend on the carbon content in the chemical composition of the steel. The hardness in the graph for 99.9% martensite content described on page 166 of Non-Patent Literature 1, "8.4.8 Method for determining martensite content from hardness and carbon content," is considered to be the hardness of martensite. Based on this graph, the hardness of martensite HV is calculated. M It is approximated by the following equation (C). HV M =942.89 × (C 0.4646 ) (C) Here, "C" in equation (C) is replaced with the mass percentage of C content in the chemical composition of the steel.

[0045] Furthermore, the hardness (HV) of bainite in steel after low-temperature tempering. B The tensile strength of bainite is σ B When given (MPa), it is expressed by the following formula (D) based on formula (2) described in Non-Patent Document 2. HV B = 0.301 × σ B +5.701 (D) Furthermore, the tensile strength σ of bainite B Based on formula (2) described in Non-Patent Document 3, it is expressed by the following formula (E). σ B = 1046 × C eq. +150 (E) Here, C in equation (E) eq. This is the carbon equivalent represented by formula (1) described in Non-Patent Document 3. Specifically, the carbon equivalent C eq. This is expressed by the following equation (F). C eq. =C+(1 / 10)×Si+(2 / 11)×Mn+(1 / 5)×Cr+(1 / 3)×V+(1 / 6)×Mo 1 / 2 (F) Here, each element symbol in equation (F) is substituted with the mass percentage content of the corresponding element in the chemical composition of the steel, and if the element is not present, "0" is substituted for the corresponding element symbol. Rearranging equations (D) to (F) above, we get the hardness of bainite HV. BThis can be determined based on the chemical composition of the steel using the following formula (G). HV B =314.85×(C+(1 / 10)×Si+(2 / 11)×Mn+(1 / 5)×Cr+(1 / 3)×V+(1 / 6)×Mo 1 / 2 ) + 50.851 (G)

[0046] From formulas (C) and (G), the hardness of martensite HV M and the hardness of bainite HV B To calculate the chemical composition of the stepped annular member 100, the chemical composition of the band-shaped region p is determined. Specifically, a test piece is taken from the member body 30, with the longitudinal section serving as the measurement surface. The measurement surface includes a rectangular measurement area with an axial length of 1000 μm and a radial length of 1000 μm, centered at the thickened portion center position 23. The measurement surface is mirror-polished. Surface analysis using EPMA is performed on the measurement area of ​​the mirror-polished measurement surface. In the surface analysis, the mass percent concentrations of C, Si, Mn, Cr, V, and Mo are measured in each of the 160,000 measurement areas, which are obtained by dividing the measurement area into 400 sections axially and 400 sections radially. For each element measured, the arithmetic mean of the elemental concentration in all measurement areas is calculated. The obtained value is defined as the content (mass %) of that element in the chemical composition of the band-shaped region p. In the EPMA surface analysis, the acceleration voltage is 15 kV, the electron beam probe spot size is 20 μm, and the probe current is 5 × 10⁻⁶ -7 Let A be the case. The measurement time in each measurement area shall be 0.05 s or longer. A calibration curve using standard EPMA test specimens may be used to convert the detected characteristic X-rays to the concentrations of each element. Based on the chemical composition of the obtained band-shaped region p, the hardness HV of martensite is calculated from formula (C). M The hardness of bainite HV is calculated from formula (G). B Calculate.

[0047] Furthermore, the Vickers hardness HV is measured in rectangular regions p1 to p25. Specifically, a test piece is taken from the member body 30, with one of the longitudinal sections, straddling the central axis X, as the measurement surface. The measurement surface is mirror-polished. At the center of each of the rectangular regions p1 to p25 on the measurement surface of the test piece, the Vickers hardness HV is measured using a method compliant with JIS Z 2244 (2009) with a measurement load of 98.07 N (10 kgf). The Vickers hardness HV obtained at the center of each rectangular region is taken as the Vickers hardness HV for that rectangular region.

[0048] Based on the Vickers hardness HV obtained in each rectangular region, the bainite fraction XB (%) in each rectangular region is calculated from equation (B). Note that the Vickers hardness HV in each rectangular region is equal to the hardness HV of martensite. M If the above is true, the bainite fraction XB is set to 0%, and the Vickers hardness HV in each rectangular region is equal to the hardness HV of bainite. B The bainite fraction XB is set to 100% in the following cases:

[0049] [Analysis example] Using the stepped annular member 100 of this embodiment as a model, the amount of deformation of the stepped annular member 100 was analyzed by heat treatment simulation using the finite element method when the distribution of bainite fraction in the band-shaped region p obtained by carburizing and quenching treatment was varied in various ways.

[0050] In the analysis, two types of shapes, shape numbers 1 and 2, were used as models for the stepped annular member 100. The inner radius rI of the member body 30 was fixed at 20 mm, the axial length h1 of the thin-walled section 10 was fixed at 30 mm, and the axial length h2 of the thick-walled section 20 was fixed at 20 mm, while the wall thickness t1 of the thin-walled section 10 and the wall thickness t2 of the thick-walled section 20 were varied as shown in Table 1.

[0051] [Table 1]

[0052] The analysis software used was Abaqus (product name) manufactured by Dassault Systèmes K.K. In the analysis example, the conditions for carburizing and quenching were fixed, and the hardenability of the member body 30 of the stepped annular member 100 used as a model was changed to obtain various distributions of bainite fraction in the band-shaped region p. Specifically, in the chemical composition of the steel that forms the member body 30 of the stepped annular member 100 used as a model, the content of elements other than C was fixed within the range corresponding to SCM420 as specified in JIS G 4053 (2018). Then, models with chemical compositions in which the C content was varied at five levels—0.15%, 0.20%, 0.25%, 0.30%, and 0.40% by mass—were prepared for each shape number. In other words, the analysis example was performed using a total of 10 different models. Furthermore, for each shape number, the distribution of bainite fraction in the band region p in the analysis results using five different models with varying carbon content in the chemical composition of the steel will be referred to as distribution A, distribution B, distribution C, distribution D, and distribution E, in order from the lowest carbon content in the chemical composition.

[0053] In the analysis example, for mechanical properties, values ​​corresponding to the chemical composition of the member body 30 were obtained by linear interpolation from experimental values ​​of steel materials having the chemical composition corresponding to SCM420, and chemical compositions in which the carbon content was changed to 0.4%, 0.6%, and 0.8% by mass%, respectively. For thermal properties, calculated values ​​derived from a chemical composition consisting of C:0.18%, Si:0.25%, Mn:0.75%, P:0.015%, S:0.015%, Ni:0.125%, Cr:1.05%, Mo:0.2%, and the remainder being Fe were used.

[0054] The simulated carburizing and quenching conditions are shown in Figure 9. Specifically, the stepped annular member 100 was first heated to 920°C and held for 120 minutes in an atmosphere with a carbon potential (CP) of 0.9%. Then, while maintaining the atmosphere with a carbon potential of 0.9%, it was cooled to 840°C and held for 30 minutes. After the holding time, the stepped annular member 100 was oil-cooled using oil at 60°C. The heat transfer coefficient of the oil used for oil cooling is shown in Figure 10.

[0055] In the stepped annular member 100 after heat treatment simulations performed under the above conditions, the total area ratio of the hard structure consisting of martensite and / or bainite in the core 50 was 95% or more in all model analysis results. Furthermore, the bainite fraction XB (%) in rectangular regions p1 to p25 was determined based on the analysis results. From the bainite fraction XB obtained in each rectangular region, the maximum value XB of the bainite fraction in rectangular regions p1 to p25 was determined. MAX (%) and the maximum value of the difference ΔXB between the bainite fractions ΔXB between adjacent rectangular regions pn and p(n+1). MAX The percentages (%) were calculated. The obtained values ​​are shown in Table 1.

[0056] Furthermore, the shape of the stepped annular member 100 after heat treatment simulation under each condition was analyzed, and the minimum (mm) and maximum (mm) values ​​of the inner diameter of the member body 30 in the axial direction were determined. The difference between the maximum and minimum values ​​was then calculated, and the resulting value was defined as the variation in inner diameter deformation (mm). The variation in inner diameter deformation for each model is shown in Table 1.

[0057] Referring to Table 1, when the stepped annular member 100 has the shape of shape number 1, the variation in the amount of internal diameter deformation was minimized when the distribution of bainite fraction in the band-shaped region p was distribution B, which satisfies conditions 1 and 2 above. Also, when the stepped annular member 100 has the shape of shape number 2, the variation in the amount of internal diameter deformation was minimized when the distribution of bainite fraction in the band-shaped region p was distribution D, which satisfies conditions 1 and 2 above. In other words, regardless of whether the stepped annular member 100 has the shape of shape number 1 or shape number 2, the variation in the amount of internal diameter deformation was minimized when the distribution of bainite fraction in the band-shaped region p satisfies conditions 1 and 2 above.

[0058] In the model of the stepped annular member 100 used in this analysis, the inner circumferential surface 31 was a smooth circular surface. In other words, no splines or other machining were applied to the inner circumferential surface 31. Furthermore, the shapes of the outer circumferential surface 12 of the thin-walled portion 10 and the outer circumferential surface 22 of the thick-walled portion 20 in the cross-section were both circular. In other words, no multiple teeth were formed on the outer circumferential surface 12 of the thin-walled portion 10 and the outer circumferential surface 22 of the thick-walled portion 20. However, even if the analysis is performed using a model in which splines or other machining are applied to the inner circumferential surface 31, or a model in which multiple teeth are formed on at least one of the outer circumferential surface 12 of the thin-walled portion 10 and the outer circumferential surface 22 of the thick-walled portion 20, the same results as in this analysis example can be obtained. The reason for this is as follows: Surfaces with teeth or grooves have increased surface area, which promotes cooling. However, the surface area of ​​the inner circumferential surface 31 is small in proportion to the total surface area of ​​the stepped annular member. Therefore, the presence or absence of teeth or grooves formed by splinting or other processes on the inner circumferential surface 31 has little effect on the analysis results. Furthermore, in cases where multiple teeth are formed on at least one of the outer circumferential surface 12 of the thin-walled portion 10 and the outer circumferential surface 22 of the thick-walled portion 20, in this embodiment, the radial distance from the central axis X to the tooth root is defined as the outer radius. When multiple teeth are formed on the outer circumferential surfaces 12 and 22, the tooth tips are preferentially cooled at the start of cooling, and the cooling of the tooth roots begins later than the tooth tips. As a result, the cooling-promoting effect of the outer circumferential surfaces 12 and 22 due to the formation of multiple teeth is substantially canceled out. Therefore, the presence or absence of multiple teeth formed on the outer circumferential surfaces 12 and 22 has little effect on the analysis results.

[0059] As described above, the stepped annular member of this embodiment having the shape described above has a total area ratio of 95% or more of the hard structure consisting of martensite and / or bainite in the core portion 50, and satisfies the above conditions 1 and 2, so the axial variation in the amount of deformation of the inner diameter due to heat treatment strain is small.

[0060] The embodiments of this disclosure have been described above. However, the embodiments described above are merely examples for implementing this disclosure. Therefore, this disclosure is not limited to the embodiments described above, and the embodiments described above can be modified as appropriate without departing from the spirit of this disclosure. [Explanation of Symbols]

[0061] 100: Stepped annular member 30: Main component 40:Carburized layer 10: Thin-walled section 20: Thick wall part X: Central axis

Claims

1. The member body is made of steel, has a constant inner diameter and an axial length of h (mm) in the axial direction, has a carburized layer formed on its surface, and in the region inside the carburized layer, the total area ratio of a hard structure consisting of martensite and / or bainite is 95% or more, and comprises an annular member body. The aforementioned member body is An annular thin-walled portion having a wall thickness t1 (mm), It includes an annular thick-walled portion that is arranged coaxially with the thin-walled portion and in contact with the thin-walled portion, and has a thickness t2 (mm) that is more than 1 to 3 times the thickness t1, In one of the cross-sections of the member body, which includes the central axis of the member body and is arranged spaced apart with respect to the central axis, When a strip-shaped region with a radial width of h / 25 mm and an axial length of h mm, with its center line at a position t1 / 2 (mm) radially from the inner circumferential surface of the member body, is divided into 25 rectangular regions arranged in the axial direction, the maximum value of the bainite fraction in each of the rectangular regions is 50% or more, and the maximum difference in the bainite fraction between two adjacent rectangular regions is 5 to 15%. Stepped annular member.

2. A stepped annular member according to claim 1, Multiple teeth are formed on at least one of the outer circumferential surfaces of the thin-walled portion and the outer circumferential surface of the thick-walled portion, along the circumferential direction of the thin-walled portion or the thick-walled portion. Stepped annular member.

3. A stepped annular member according to claim 1 or claim 2, Spline teeth grooves, keyways, or screw grooves are formed on the inner circumferential surface of the member body. Stepped annular member.

Citation Information

Patent Citations

  • Gear and manufacturing method for gear

    JP2019143211A